Variations in erythrogram, osmatic fragility and plasma electrolyte concentration due to anaemia in goats - RASTOGI, S K; MITRA, S; KUMAR, NARESH; KUMAR, R (The Indian Journal of Animal Sciences, 2013)
Erythrocytic indices, osmotic fragility and plasma electolyte conectration were studied in 6 healthy kids and 10 clinically anaemic kids of undefined aetiology. Mean haemoglobin concentration, packed. cell volume and total erythrocyte count were recorded as 4.75±0.21 g/dl, 18.4±1.0% and 8.56±0.55 million/alphai in anaemic goats compared to the corresponding values of 8.15±0.34, 27.7± 1.22 and 17.8±1.23 in healthy kids. The mean values of MCH and MCV were higher, and that of MCHC lower in the kids suffering from anaemia. Red blood cells from anaemic kids were more susceptible to osmotic lysis between saline concenfrations of 0.70 and 1.00% with mean corpuscular fragility values of 0.709±0.043% and 0.734±b.021 % in the healthy and anaemic kids respectively. Plasma concentration of sodium, potassium, chloride and total proteins, however, did not differ significantly in the two group studied.